2019
DOI: 10.1111/tbed.13221
|View full text |Cite
|
Sign up to set email alerts
|

Does porcine circovirus type 3 (PCV3) interfere with porcine circovirus type 2 (PCV2) vaccine efficacy?

Abstract: PCV2 is globally spread pathogen involved in a number of diseases (PCVD). Commonly used vaccines against PCV2 are proved to be highly efficacious. The role of recently discovered PCV3 for pig health and interference with PCV2 remains unknown. The study performed on serum samples from seven farms vaccinated against PCV2 and four non-vaccinated showed very low prevalence of PCV2 viremia in the former (3 out of 106 positive serum pools) and high prevalence of PCV2 viremia in the latter (35 out of 60 positive pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 45 publications
2
27
1
Order By: Relevance
“…Subclusters have only been suggested by several authors who have compared PCV3's complete genomes; if our partial genome isolates are compared to their closest relatives, our sequences could be placed in either the PCV3a-IM subcluster or the PCV3b subcluster. It had been suggested that PCV2-PCV3 cross-protection might occur [21], though we did not expect it, nor was it found to occur.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Subclusters have only been suggested by several authors who have compared PCV3's complete genomes; if our partial genome isolates are compared to their closest relatives, our sequences could be placed in either the PCV3a-IM subcluster or the PCV3b subcluster. It had been suggested that PCV2-PCV3 cross-protection might occur [21], though we did not expect it, nor was it found to occur.…”
Section: Discussioncontrasting
confidence: 60%
“…On the other hand, this may suggest that infection is mostly subclinical or only clinically visible when co-factors enhance the primary effect of PCV3 [12]. The genomes of PCV2 and PCV3 are identical up to 37% and this raises questions concerning possible cross-immunogenicity [21]; in that case, anti-PCV2 vaccination should also eliminate or reduce PCV3 virus burden [15,22]. Since swine circovirus associated diseases are a problem faced by Slovenia's pig producers [23], we considered it likely that PCV3 was also present on Slovenian farms.…”
Section: Introductionmentioning
confidence: 99%
“…Samples with Ct values ≤37 were considered positive. The quantification of viral genome copies was performed using titrated plasmids containing ORF2 of PCV2 [33]. Viral titers inferred from the real-time PCR results are expressed as the log 10 viral copy number per milliliter of pool or oral fluid (copies/mL).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…w/o suckling piglets, but this was not supported statistically [21]. We also vaccinated and tested a small group of animals in which PCV3 was discovered on Farm 5 and found that, while the number of PCV2-positive samples fell slightly, no noticeable change in PCV3 presence occurred.…”
Section: Woźniak Et Al Reported a Slight Reduction In Pcv3 And Circomentioning
confidence: 86%
“…The genomes of PCV2 and PCV3 are identical up to 37% and this raises questions concerning possible cross-immunogenicity [21]; in that case, anti-PCV2 vaccination should also eliminate or reduce PCV3 virus burden [15,22]. Since swine circovirus associated diseases are a problem faced by Slovenia's pig producers [23], we considered it likely that PCV3 was also present on Slovenian farms.…”
mentioning
confidence: 99%